Audio describing films: A first look into the description process - Jankowska, Anna (The Journal of Specialised Translation, 2021)
This article uses the data gathered in an experiment carried out to investigate audio description decision-making processes to analyse the scripting process of audio description for films. As part of the study, describers from Poland and Spain prepared audio description for ten clips from Polish and Spanish films. Data was collected through a multi-method approach, which included keylogging, think-aloud verbalisations, screen and face recording. Results, based on a qualitative analysis of screen and face recordings and think-aloud protocols, show that the audio description scripting process resembles operations involved in both writing and translating, and may be divided into three main processes (pre-drafting, drafting and post-drafting) and seven intertwining subprocesses (understanding, planning, searching, generating text, revising, reviewing, and cueing).